Location of the root canal: Direct vision versus surgical microscope. In-vitro study. - Gabriela Sánchez; Marcela Alegría; David Pesce; Raúl Alcántara (Universidad de Concepción., 2012)
The inability to properly identify the entrance to the root system, main and accessories, is one of the causes of endodontic failure. Hence arises the need to incorporate new technologies to improve the visibility of the access cavity to the location of the entrance to one of the root. The purpose of this study was to compare whether there is a difference between the location of root canals of human permanent molars through direct vision and using the surgical microscope. We examined 100 extracted human permanent molars first by direct vision and then using a surgical microscope to determine the number of root canals located. The difference was established for obtaining the real number of channels to make the cut root. Our study indicates that the number of root canals located increase in a 11% with the use of surgical microscope which is reflected in special conduits accessories which is consistent with other studies performed. It can be concluded from this study that the use of a surgical microscope were located a greater number of ducts in relation to the use of direct vision therefore is considered a useful tool to aid the clinician inconventional endodontic treatment, offering a fully operative fieldilluminated and magnified viewing with great detail, the floor of the chamber and the entrance to all canals, which is the key to success in endodontics.